PROBIOTICS AND INSULIN AUTOIMMUNE SYNDROME - Ng, Yong Siang; Goh, Qing Ci; Mak, Woh Wei; Krishnan, Gayathri Devi; Ng, Yoke Mui; Redzuan, Shazatul Reza Mohd; Rajoo, Subashini; Bidin, Mohamed Badrulnizam Long (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Insulin autoimmune syndrome (IAS) is characterized by positive insulin autoantibodies and recurrent hyperinsulinaemic hypoglycaemia in someone without diabetes as well as no prior insulin exposure. The association between probiotics and IAS has not been reported in literature. Here we describe a case of IAS induced by a probiotic supplement. CASE A 74-year-old female presented with reduced consciousness and low blood glucose (2.1 mmol/L) after taking molasses drinks the night before. She had no diabetes. During hospitalization, she experienced multiple episodes of hypoglycaemia (usually occurring postprandially) and a thorough workup revealed inappropriately elevated serum insulin levels, serum C-peptide, and the presence of insulin autoantibodies. The molasses drink tested negative for sulfonylureas. There were no identified risk factors for IAS except she had been taking one type of probiotic pills for 2 months prior to the hospitalization. The probiotic was discontinued, and she was managed conservatively with the advice of taking a small, frequent, and low carbohydrate diet. She returned for a follow-up visit later with no more hypoglycaemia events. IAS is a rare hypoglycaemic disorder with hypoglycaemia episodes that occur mainly postprandially. It is frequently reported in the East Asian population and its incidence is mounting due to increased awareness of the condition. IAS is commonly triggered by drugs (e.g., methimazole, alpha lipoic acid), and most cases have coexisting autoimmune disorders (e.g., Graves’ disease, systemic lupus erythematosus, rheumatoid arthritis). Fortunately, IAS is usually self-limiting with good outcomes after discontinuing the offending agents or stabilizing the coexisting autoimmune diseases. CONCLUSION To our knowledge, this is the first case that highlighted the association between probiotic supplementation and IAS. Further studies to underpin the association and mechanisms are required.